Assessment the Unconfined Aquifer Resources Under Climate Change Impacts: Case Study of Akkar Plain - القاموع , ديالا; شريف حايك; منذر حماد (Latakia University Journal -Engineering Sciences Series, 2023)
Assessing the impact of climate change on groundwater recharge is crucial for depicting the vulnerability of water resources and identifying proper adaptation measures. This study used Soil and Water Assessment Tool (SWAT) to simulate the impact of climate change on groundwater recharge and streamflow in Al-Abrash downstream catchment which is located in Akkar Plain. The model performance was tested for monthly flow under a ten-year calibration period (2004–2014). Climate predictions was used from the synthetic weather generator WGEN under two climate scenarios (RCP4.5, and RCP8.5). The result of study indicated satisfactory precision in fitting observed and simulated flow using statistical indices. The model indicated that for winter conditions the scenarios predict an increase in water levels and a considerable decrease during summer, the average annual recharge of groundwater will decrease by around (26–28) % in the near future (2021–2040) under the two RCP future scenarios.